Functioning and mechanisms of PTMs in renal diseases - Liu, Zhenzhen; Yang, Jian; Du, Minghui; Xin, Wei (Frontiers in Pharmacology, 2023)
Post-translational modifications (PTMs) are crucial epigenetic mechanisms that regulate various cellular biological processes. The use of mass spectrometry (MS)-proteomics has led to the discovery of numerous novel types of protein PTMs, such as acetylation, crotonylation, 2-hydroxyisobutyrylation, β-hydroxybutyrylation, protein propionylation and butyrylation, succinylation, malonylation, lactylation, and histone methylation. In this review, we specifically highlight the molecular mechanisms and roles of various histone and some non-histone PTMs in renal diseases, including diabetic kidney disease. PTMs exhibit diverse effects on renal diseases, which can be either protective or detrimental, depending on the specific type of protein PTMs and their respective targets. Different PTMs activate various signaling pathways in diverse renal pathological conditions, which could provide novel insights for studying epigenetic mechanisms and developing potential therapeutic strategies for renal diseases.